體減薏苡仁湯의 항비만 효과 연구 - 박태용(Tae Yong Park); 신병철(Byung Cheul Shin); 공재철(Jae Cheol Kong); 송미영(Mi Young Song); 김은경(Eun Kyung Kim); 서은아(Eun A Seo); 류도곤(Do Gon Ryu); 권강범(Kang Beom Kwon) (동의생리병리학회지, 2008)
The aim of this study is to investigate Chegameuiin-tang water extracts (CETE) have potent anti-obesity activities in a high fat diet-induced obesity mouse model. In this study, we designed three group (normal diet group, high fat diet group, high fat diet plus CETE group for 13-week oral administration). Increases in body weight and fat storage were inhibited by 13-week oral administration of CETE at a 500 mg/kg concentration in this animal model, while the amount of food intake was not affected. Results from blood lipid analysis showed that the levels of triglyceride, total cholesterol and LDL-cholesterol were significantly lowered by CETE administration, also HDL-cholesterol was increased more than high fat diet-induced obese mouse. To understand the underlying mechanism at the molecular level, the effects of CETE were examined on the expression of the genes involved in lipogenesis and lipolysis by real-time PCR. In epididymal fat of CETE-treated mice, the mRNA level of lipogenic genes such as sterol regulatory element binding protein 1 and fatty acid synthase were decreased, which was well correlated with the reduction of the epididymal fat weight. Also, CETE administration inhibited decreases of the hormone-sensitve lipase and lipoprotein lipase mRNA expressions, which are genes related with lipolysis. These results suggest that Chegameuiin-tang may have great potential as a novel anti-obesity agent. KCI Citation Count: 5